A model of near-surface coupled-flow effects on the diurnal thermal regime of a peat-covered palsa - Nelson, Frederick E.; Outcalt, Samuel I. (Archives for Meteorology, Geophysics, and Bioclimatology Series A, 1985)
The thermal regime in the moist surficial peat layer of a palsa, measured during a clear and calm July day in arctic Alaska, indicates that coupled heat and water flow retard ablation of the ice core. A simulation model of coupled-flow effects was constructed using rough estimates of meteorological boundary conditions and material properties. The model indicates that ablation is inhibited by advection of cold water above the ice/peat interface, and by internal evaporation near the surface. Evaporation also limits thermal maxima near the surface; because the ratio of the heat of evaporation to the heat of fusion is approximately 7.5, the coupled-flow regime effectively retards ablation of the palsa's ice core. Das Temperaturregime in der feuchten, oberflächennahen Torfschicht eines Pals wurde während eines klaren und windstillen Julitages in der Arktis von Alaska vermessen. Es wird gezeigt, daß der gekoppelte Wärme- und Wasserstrom die Ablation des Eiskernes verzögert. Ein Simulationsmodell der gekoppelten Stromeffekte wurde konstruiert, wobei grobe Abschätzungen der meteorologischen Grenzbedingungen und der Bodenbeschaffenheit angebracht wurden. Das Modell deutet an, daß die Ablation durch Advektion von kaltem Wasser oberhalb der Eis-Torf-Grenzschicht und durch interne Verdunstung nahe der Oberfläche behindert wird. Verdunstung beschränkt außerdem die Temperaturmaxima nahe der Oberfläche. Da das Verhältnis der latenten Wärmen der Verdunstung und der Sublimation ungefähr 7,5 beträgt, verzögert das gekoppelte Stromregime effektiv die Ablation des Eiskernes der Pals. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/41663/1/703_2005_Article_BF02258484.pdf